Sikap Menghormati Orang Tua Melalui Refleksi Keluaran 20:12 Demi Terwujudnya Kesejahteraan Lansia - Piter Imanson Damanik; Marta Regina Silvi Simanungkalit; Martina Novalina (Sekolah Tinggi Teologi Ekumene Jakarta., 2021)
Honoring one's parents is the fifth of the ten commandments of God found in the book of Exodus. Over time, the attitude of respect for parents has decreased which is quite alarming. This is marked by the emergence of phenomena and cases that occur in neglected elderly and do not receive adequate services by their families and relatives around them. This study aims to provide an understanding and implications of the text output 20:12 so that readers have more respect for the elderly in the family and community environment. The method used is qualitative with a literature study approach related to the attitude of respect for the elderly contained in Exodus 20:12 to explain how to respect parents, especially the elderly. The results obtained are that Exodus 20:12 reflects the true respect for the elderly where it can be a guide for the welfare of the elderly in Indonesia, especially the Christian elderly. This respect is realized through the understanding that children as part of the family are not only supportive as a support system from the physical side but also spiritually.